REVIEW OF ISLAMIC ECONOMIC LAW ON THE PRACTICE OF SAWERIA ON YOUTUBE - Muhammad Hafid Siddiq; Muslim; Aulil Amri (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2021)
Website platforms can make it easier for people to give alms through their respective gedgets, one of which is Youtube, being one of the most accessed sites both as viewers and as content creators. Youtube has also produced many wealthy people through uploading videos, to cover the declining income, many content creators use crowdfunding so that they can get online donation income by listing donation links in the descriptions of the videos they make. Saweria is here as a crowdfunding website for fundraising and donating online which is being used by many YouTubers in their live streams on YouTube. The ease of using Saweria access can cause problems in the future if it is used incorrectly. The purpose of this research activity was to find out the aspects of Fiqh Muamalah to Saweria practice on YouTube, as well as to find out the ideal setting regarding Saweria practice on YouTube. This research method uses a descriptive method of analysis. This research uses an empirical approach by conducting research using field research and literature research. In crowdfunding transactions it is difficult to know whether the recipient of the funds is a person in the circumstances as described. So is the company profile whether fictitious or true. The opportunity for transactions that use non-identity is actually very possible, The opportunity for transactions that use non-identity identity is very possible. If so it is booked then the contract becomes invalid.